Catalytic asymmetric chemoselective 1, 3-dipolar cycloadditions of an azomethine ylide with isatin-derived imines: diastereo- and enantioselective construction of a spiro[imidazolidine-2, 3′-oxindole] framework. Issue 9 (4th November 2015) - Wang, Yue-Ming; Zhang, Hong-Hao; Li, Can; Fan, Tao; Shi, Feng
Abstract : The title reaction has been established to construct biologically important spiro[imidazolidine-2, 3′-oxindole] frameworks in high diastereo- and enantioselectivities. Abstract : A catalytic asymmetric chemoselective 1, 3-dipolar cycloaddition (1, 3-DC) of an azomethine ylide with imines has been established via a three-component reaction of isatin-derived imines, aldehydes and an amino-ester in the presence of chiral phosphoric acid, which efficiently constructed biologically important spiro[imidazolidine-2, 3′-oxindole] frameworks in good yields, and with high diastereo- and enantioselectivities (up to 76% yield, 97 : 3 er, all >95 : 5 dr). This reaction not only realized a catalytic asymmetric chemoselective 1, 3-DC of an azomethine ylide, but also represented the first enantioselective construction of a spiro[imidazolidine-2, 3′-oxindole] skeleton.